Fe-Ni based titanium carbide coating alloy powder for laser cladding and Fe-Ni based titanium carbide coating
By using Fe-Ni-based titanium carbide coated alloy powder and combined with laser cladding process, the existing laser cladding coating problem is solved, and a coating preparation with high hardness, high wear resistance and low cost is achieved.
Patent Information
- Application Number
- CN202310137736.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-02-20
AI Technical Summary
The hardness and wear resistance of the existing laser cladding coatings have poor hardness and wear resistance, resulting in a low service life and cannot meet the requirements of the existing technology.
The Fe-Ni-based titanium carbide coated alloy powder is prepared by mixing the iron-based alloy powder, nickel-based alloy powder and TiC powder in a specific proportion, and the coating is prepared by a laser cladding process.
The prepared Fe-Ni-based titanium carbide coating has high hardness and high wear resistance, and at the same time it has low production costs. The total wear amount is <0.2g under a load of 2000g for 60 hours.
Smart Images

Figure CN116060614B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cladding coating powder, in particular to a Fe-Ni based titanium carbide coating alloy powder for laser cladding and a Fe-Ni based titanium carbide coating. Background Art
[0002] Plasma cladding technology and laser cladding technology are common and effective surface modification technologies. Both technologies use a layer of alloy coating with hard particles to be clad on the solid surface of the workpiece. Nickel-based and iron-based materials are often used as matrix materials in engineering. Tungsten carbide particles have good wettability with nickel-based alloys and are often used as important powder materials to strengthen nickel-based alloys; titanium carbide has excellent physical and chemical properties such as low density, high melting point, high hardness, wear resistance, and corrosion resistance. At the same time, titanium carbide and γ-Fe both belong to face-centered cubic structures. They have good wettability at high temperatures and do not react chemically. Therefore, titanium carbide is often used as an iron-based reinforcement phase, which can make iron-based composite materials have excellent properties such as high strength, high temperature resistance and wear resistance.
[0003] In the actual production process, due to the low price of iron powder and excellent physical and mechanical properties, it is conducive to saving production costs and ensuring high production efficiency at the same time. At the same time, Ti is often associated with Fe, and the price of Ti / Fe powder is low. It is used as the reinforcement phase of Fe-based materials. TiC is quite suitable. TiC has the characteristics of high hardness, high modulus and good chemical stability. Therefore, iron-based alloy powder and TiC powder are often selected to be compounded as laser cladding powder to prepare laser cladding coatings. However, although this laser cladding coating has a lower cost, the hardness and wear resistance of the coating are poor, resulting in a lower service life, which can no longer meet the requirements of the existing technology.
[0004] Therefore, providing an alloy powder for laser cladding that has good hardness and wear resistance and low production cost has become a technical problem that needs to be urgently solved in this field. Summary of the invention
[0005] The purpose of the present invention is to provide an Fe-Ni based titanium carbide coating alloy powder for laser cladding and an Fe-Ni based titanium carbide coating. The Fe-Ni based titanium carbide coating prepared by using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided by the present invention has high hardness and high wear resistance, and the production cost is relatively low.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a Fe-Ni based titanium carbide coating alloy powder for laser cladding, which is prepared from the following raw materials: iron based alloy powder, nickel based alloy powder and TiC powder;
[0008] The element composition of the iron-based alloy powder includes, by mass percentage, C: 3.0-4.0%, O < 0.05%, B: 1.5-2.5%, Si: 2.0-3.0%, Cr: 20-35%, Ni: 2.0-8.0%, Mo: 2.0-5.0% and the balance Fe;
[0009] The element composition of the nickel-based alloy powder includes, by mass percentage, C: 0.2-0.5%, Cr: 0.2-0.5%, B: 0.4-0.8%, Si: 1.1-1.5%, Fe: 0.3-0.6% and the balance Ni;
[0010] The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is (3-4):1.
[0011] Preferably, the content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 35-65% by mass.
[0012] Preferably, the content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 40-60%.
[0013] Preferably, the element composition of the iron-based alloy powder is: C: 3.5-3.8%, O<0.04%, B: 2.0-2.3%, Si: 2.5-2.8%, Cr: 25-30%, Ni: 4.0-6.0%, Mo: 3.0-4.0% and the balance Fe.
[0014] Preferably, the element composition of the nickel-based alloy powder is: C: 0.3-0.4%, Cr: 0.3-0.4%, B: 0.5-0.7%, Si: 1.2-1.4%, Fe: 0.4-0.6% and the balance Ni.
[0015] Preferably, the mass ratio of the iron-based alloy powder to the nickel-based alloy powder is 4:1.
[0016] Preferably, the particle size of the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 60-200 meshes.
[0017] The present invention provides an Fe-Ni based titanium carbide coating, which is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding described in the above technical solution as a raw material.
[0018] Preferably, the parameters of the laser cladding process include: laser power: 2.5-4.5KW, powder feeding amount: 12-18g / min, swing amplitude: 15-40mm, swing speed: 20-60mm / min, powder feeding gas flow rate: 5.5-8.5L / min, shielding gas flow rate: 10-15L / min.
[0019] Preferably, the parameters of the laser cladding process include: laser power: 3.0-4.0KW, powder feeding amount: 14-16g / min, swing amplitude: 20-35mm, swing speed: 30-50mm / min, powder feeding gas flow rate: 6.0-8.0L / min, shielding gas flow rate: 12-14L / min.
[0020] The invention provides an Fe-Ni based titanium carbide coating alloy powder for laser cladding, which is prepared from the following raw materials: iron-based alloy powder, nickel-based alloy powder and TiC powder; in terms of mass percentage, the element composition of the iron-based alloy powder comprises: C: 3.0-4.0%, O<0.05%, B: 1.5-2.5%, Si: 2.0-3.0%, Cr: 20-35%, Ni: 2.0-8.0%, Mo: 2.0-5.0% and the balance of Fe; in terms of mass percentage, the element composition of the nickel-based alloy powder comprises: C: 0.2-0.5%, Cr: 0.2-0.5%, B: 0.4-0.8%, Si: 1.1-1.5%, Fe: 0.3-0.6% and the balance of Ni; the mass ratio of the iron-based alloy powder to the nickel-based alloy powder is (3-4):1. In the iron-based alloy powder provided by the present invention, the content of B and Si elements is higher than that of the nickel-based alloy powder, which makes up for the defect of low B and Si elements in the single nickel-based alloy powder. The presence of B and Si elements reduces the melting point of the mixed alloy powder. The increase in the content of the two elements expands the solid-liquid phase temperature zone and forms a low-melting point eutectic during the solidification process. At the same time, B and Si elements also have the ability of deoxidation and slag formation. With the increase of B and Si elements in the iron-based alloy powder, B and Si can diffuse to the surface of a large amount of Ni during the laser cladding process, combine with oxygen to form oxides, and react with the original oxides on the surface of the substrate to form borates, so that the purity of the Fe-Ni-based titanium carbide coating alloy powder cladding layer is increased. At the same time, the increase in the content of B and Si elements can also improve the welding performance of the alloy. The Cr content in the iron-based alloy powder increases, which makes up for the defect of less Cr element in the single nickel-based alloy powder. The surplus Cr element can also form silicide and boride with B and Si elements. Hard phase, and can also form chromium carbide and chromium boride with C and B elements, thereby improving the hardness and wear resistance of the cladding layer; at the same time, a large amount of Cr element in the iron-based alloy powder makes up for the defect that the chromium boride formed by boron and chromium in the single nickel-based alloy powder will lead to chromium-poor coating; in the nickel-based alloy powder, the content of Ni element is higher than that of Ni element in the iron-based alloy powder, and the surplus Ni element can also form hard compounds with B and Si elements to improve the comprehensive performance of the cladding layer; the solid solubility of Cr in Ni can reach 40%, and the surplus Cr element in the iron-based alloy powder and the surplus Ni element in the nickel-based alloy powder will form a Ni-Cr solid solution, thereby increasing the strength of the mixed alloy powder; the presence of C element can purify the grain boundary and improve the strengthening and toughening effect of the grain boundary. The C content in the iron-based alloy powder is higher than that in the nickel-based alloy powder, and the surplus C is generally segregated at the grain boundary, which improves the distribution and morphology of the second phase on the grain boundary, thereby making up for the creep strength and plastic strength of the single nickel-based alloy;By controlling the C content, the problem of alloy powder becoming brittle and prone to cracking due to excessive C content can be avoided, thereby improving its comprehensive performance. Appropriately supplementing the C content in the iron-based alloy powder can play a synergistic role with the nickel-based alloy powder, thereby improving its mechanical properties and organizational stability; by appropriately increasing the content of B, Si, and Fe elements, while coordinating the C content with the C content of the iron-based alloy powder, the element content ratio of the nickel-based alloy powder and the iron-based alloy powder can be complementary and coordinated with each other, thereby further improving the wear resistance of the alloy powder; by controlling the dosage relationship of the iron-based alloy powder and the nickel-based alloy powder, the Ni element and the B element in the Fe-Ni-based titanium carbide coating alloy powder will form a Ni3B strengthening phase, further improving the mixed alloy powder. Comprehensive mechanical properties; under the action of the laser beam, the excess Cr, Si, Fe and other elements in the iron-based alloy powder will also dissolve in the large amount of Ni in the nickel-based alloy powder to form a γ-Ni solid solution, which plays a role in solid solution strengthening of the Fe-Ni-based titanium carbide coating; at the same time, under the effect of the element compensation of the two alloy powders, the Ni, Cr, Si, Fe, B, and C elements contained in the powder will generate a large amount of carbide and boride hard phases under the action of the laser beam, which plays a role in precipitation strengthening of the cladding coating, thereby saving process costs under the premise of wear resistance, good adhesion, and not easy to crack; TiC powder has good wettability with iron-based alloy powder and nickel-based alloy powder, thereby improving the bonding strength between the Fe-Ni-based titanium carbide coating and the substrate. The results of the embodiment show that the Fe-Ni-based titanium carbide coating prepared by the Fe-Ni-based titanium carbide coating alloy powder for laser cladding provided by the present invention is worn for 60 hours under a load of 2000g, and the total wear amount is less than 0.2g, which has excellent wear resistance. ; BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a metallographic microstructure diagram of the Fe-Ni based titanium carbide coating prepared in Application Example 1 of the present invention;
[0022] Figure 2 This is a metallographic microstructure diagram of the Fe-Ni based titanium carbide coating prepared in Application Example 2 of the present invention;
[0023] Figure 3 This is a metallographic microstructure diagram of the Fe-Ni based titanium carbide coating prepared in Application Example 3 of the present invention;
[0024] Figure 4 This is a metallographic microstructure diagram of the Fe-Ni based titanium carbide coating prepared in Application Example 4 of the present invention;
[0025] Figure 5 This is a metallographic microstructure diagram of the Fe-Ni based titanium carbide coating prepared in Application Example 5 of the present invention;
[0026] Figure 6 This is a metallographic microstructure of the Fe-Ni based titanium carbide coating prepared in Application Example 6 of the present invention;
[0027] Figure 7 The microstructure metallographic diagram of the Fe-based titanium carbide coating prepared in comparative application example 1;
[0028] Figure 8 The wear resistance test diagram of the coatings prepared in Application Example 1 and Comparative Application Example 1;
[0029] Fig. 9 This is a test chart of the wear resistance of the coatings prepared in Application Examples 7 to 8 and Comparative Application Example 2. DETAILED DESCRIPTION
[0030] The invention provides a Fe-Ni based titanium carbide coating alloy powder for laser cladding, which is prepared from the following raw materials: iron based alloy powder, nickel based alloy powder and TiC powder.
[0031] The present invention has no particular limitation on the preparation method of the iron-based alloy powder and the nickel-based alloy powder. The iron-based alloy powder and the nickel-based alloy powder can be prepared according to the common technical knowledge in the art, and the chemical composition of the iron-based alloy powder and the nickel-based alloy powder can meet the requirements. The present invention has no particular limitation on the specific source of the TiC powder. A commercial product well known to those skilled in the art can be used or the powder can be prepared by itself.
[0032] The present invention has no special limitation on the preparation method of the Fe-Ni based titanium carbide coating alloy powder for laser cladding, and it only needs to make the iron based alloy powder, the nickel based alloy powder and the TiC powder be evenly mixed.
[0033] In the present invention, the element composition of the iron-based alloy powder includes, by mass percentage, C: 3.0-4.0%, O<0.05%, B: 1.5-2.5%, Si: 2.0-3.0%, Cr: 20-35%, Ni: 2.0-8.0%, Mo: 2.0-5.0% and the balance Fe, preferably: C: 3.5-3.8%, O<0.04%, B: 2.0-2.3%, Si: 2.5-2.8%, Cr: 25-30%, Ni: 4.0-6.0%, Mo: 3.0-4.0% and the balance Fe, more preferably: C: 3.5-3.6%, O<0.03%, B: 2.0-2.1%, Si: 2.5-2.6%, Cr: 28-30%, Ni: 5.0-6.0%, Mo: 3.0-3.5% and the balance Fe. In the present invention, the average Rockwell hardness value of the iron-based alloy powder is preferably 58-62HRC, and more preferably 60HRC. In the iron-based alloy powder provided by the present invention, the content of B and Si elements is higher than that of the nickel-based alloy powder, which makes up for the defect of low B and Si elements in the single nickel-based alloy powder. The presence of B and Si elements reduces the melting point of the mixed alloy powder. The increase in the content of the two elements expands the solid-liquid phase temperature zone and forms a low-melting eutectic during the solidification process; at the same time, B and Si elements also have the ability of deoxidation and slag formation. With the increase of B and Si elements in the iron-based alloy powder, during the laser cladding process, B and Si can diffuse to the surface of a large amount of Ni, combine with oxygen to form oxides, and can also react with the original oxides on the surface of the substrate to form boron The addition of B and Si elements into the Fe-based alloy powder can improve the purity of the Fe-Ni based titanium carbide coating alloy powder cladding layer, and the increase in the content of B and Si elements can also improve the welding performance of the alloy; the increase in the Cr content in the Fe-based alloy powder makes up for the defect of less Cr element in the single Ni-based alloy powder, and the surplus Cr element can also form silicide and boride hard phases with B and Si elements, and can also form chromium carbide and chromium boride with C and B elements, thereby improving the hardness and wear resistance of the cladding layer; at the same time, the large amount of Cr element in the Fe-based alloy powder makes up for the defect that the chromium boride formed by boron and chromium in the single Ni-based alloy powder will lead to chromium-poor coating.
[0034] In the present invention, the element composition of the nickel-based alloy powder includes, by mass percentage, C: 0.2-0.5%, Cr: 0.2-0.5%, B: 0.4-0.8%, Si: 1.1-1.5%, Fe: 0.3-0.6% and the balance of Ni; preferably, C: 0.3-0.4%, Cr: 0.3-0.4%, B: 0.5-0.7%, Si: 1.2-1.4%, Fe: 0.4-0.6% and the balance of Ni; more preferably, C: 0.3-0.35%, Cr: 0.3-0.35%, B: 0.6-0.7%, Si: 1.3-1.4%, Fe: 0.5-0.55% and the balance of Ni. In the present invention, the average Rockwell hardness value of the nickel-based alloy powder is preferably 52-55HRC, more preferably 54HRC. The present invention controls the composition of the nickel-based alloy powder, so that the powder has the advantages of good corrosion resistance, oxidation resistance, heat resistance, low stress abrasive wear resistance, good impact toughness, low melting point, wide solid-liquid mutual temperature range, etc.; the content of Ni element in the nickel-based alloy powder is higher than that of Ni element in the iron-based alloy powder, and the surplus Ni element can also form hard compounds with B and Si elements to improve the comprehensive performance of the cladding layer; the solid solubility of Cr in Ni can reach 40%, and the surplus Cr element in the iron-based alloy powder and the surplus Ni element in the nickel-based alloy powder will form a Ni-Cr solid solution, thereby increasing the strength of the mixed alloy powder; the presence of C element can purify the grain boundary and improve the strengthening and toughening effect of the grain boundary, and C in the iron-based alloy powder The C content is higher than that of nickel-based alloy powder, and the surplus C is generally segregated at the grain boundary, which improves the distribution and morphology of the second phase on the grain boundary, thereby making up for the creep strength and plastic strength of the single nickel-based alloy; by controlling the C content, the problem of alloy powder becoming brittle and prone to cracks due to excessive C content can be avoided, thereby improving its comprehensive performance, and appropriately supplementing the C content in the iron-based alloy powder can play a synergistic role with the nickel-based alloy powder, thereby improving its mechanical properties and organizational stability; by appropriately increasing the content of B, Si, and Fe elements, and at the same time coordinating the C content with the C content of the iron-based alloy powder, the element content ratio of the nickel-based alloy powder and the iron-based alloy powder can be made complementary and coordinated with each other, thereby further improving the wear resistance of the alloy powder.
[0035] In the present invention, the mass ratio of the iron-based alloy powder to the nickel-based alloy powder is (3-4):1, preferably (3.5-4):1, and more preferably 4:1. The present invention controls the amount relationship of the iron-based alloy powder and the nickel-based alloy powder, and the Ni element and the B element in the Fe-Ni-based titanium carbide coating alloy powder will form a Ni3B strengthening phase, further improving the comprehensive mechanical properties of the mixed alloy powder; under the action of the laser beam, the excess Cr, Si, Fe and other elements in the iron-based alloy powder will also be dissolved in a large amount of Ni in the nickel-based alloy powder to form a γ-Ni solid solution, which plays a role in solid solution strengthening of the Fe-Ni-based titanium carbide coating; at the same time, under the action of the element compensation of the two alloy powders, the Ni, Cr, Si, Fe, B, and C elements contained in the powder will generate a large amount of carbide and boride hard phases under the action of the laser beam, which plays a role in precipitation strengthening of the cladding coating, thereby saving process costs under the premise of wear resistance, good adhesion, and not easy to crack.
[0036] In the present invention, the content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is preferably 35-65%, more preferably 40-60%, and further preferably 50-55% by mass percentage. In the present invention, the average Rockwell hardness value of the TiC powder is preferably 60-65HRC, and more preferably 62HRC. By adding TiC powder, the present invention takes advantage of the low solubility of TiC in Fe-based materials, and has an inherent advantage in preparing Fe-Ni based titanium carbide coating materials with excellent performance. At the same time, the advantages of high melting point, high hardness, high wear resistance and good wettability of titanium carbide with iron alloy substrate are combined to further improve the bonding strength between Fe-Ni based titanium carbide coating and substrate; by controlling the amount of TiC powder, during the laser cladding process, the undissolved TiC in the alloy powder is dispersed in the coating as a hard phase, which plays a role of dispersion strengthening, and further improves the comprehensive performance of Fe-Ni based titanium carbide coating alloy powder.
[0037] In the present invention, the particle size of the iron-based alloy powder is preferably 60-200 mesh, more preferably 80-180 mesh, and further preferably 80-150 mesh; the particle size of the nickel-based alloy powder is preferably 60-200 mesh, more preferably 80-180 mesh, and further preferably 80-150 mesh; the particle size of the TiC powder is preferably 80-120 mesh; the particle size of the Fe-Ni-based titanium carbide coating alloy powder for laser cladding is 60-200 mesh, more preferably 80-180 mesh, and further preferably 80-150 mesh. By controlling the particle size of the alloy powder, the present invention can make the Fe-Ni-based titanium carbide coating alloy powder meet the technical requirements of the laser cladding process, reduce the defects inside the coating during the laser cladding process, and thus further improve the comprehensive performance of the Fe-Ni-based titanium carbide coating.
[0038] The present invention combines the cladding advantages of different materials, uses iron-based alloy powder, nickel-based alloy powder and TiC powder as raw materials, and controls their specific composition and ratio to obtain Fe-Ni-based titanium carbide coating alloy powder for laser cladding, combines the advantages of high hardness, good wear resistance and low cost of the iron-based titanium carbide cladding layer with the advantages of no cracks and good adhesion of the nickel-based tungsten carbide cladding layer, utilizes the complementarity of the two alloy powder elements, supplements the elements lacking in each other, is more conducive to the formation of cemented carbide compounds, and improves the hardness and wear resistance of the cladding layer; TiC powder and iron-based alloy powder have good chemical wettability, and no chemical reaction occurs at the interface; at the same time, TiC powder and nickel-based alloy powder have relatively good wettability, through TiC powder By adjusting the powder, the nickel-based alloy powder has a good wettability to the substrate, a strong bonding force with the substrate, and can be metallurgically bonded with the substrate, thereby improving the adhesion between the Fe-Ni-based titanium carbide coating and the substrate; by controlling the ratio of the alloy powder, the hardness and wear resistance of the Fe-Ni-based titanium carbide coating alloy powder are in the middle position of the two single alloy-based powders. On the premise that the hardness and wear resistance meet the actual needs of the project, the problems of easy cracking, low hardness, poor wear resistance, poor adhesion and high cost of the single cladding layer are solved. On the premise that the cladding layer has a high hardness while having good toughness, wear resistance, adhesion and is not easy to crack, the process cost is saved, the applicability is good, and it meets the actual needs of the project.
[0039] The present invention provides an Fe-Ni based titanium carbide coating, which is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding described in the above technical solution as a raw material.
[0040] In the present invention, the parameters of the laser cladding process preferably include: laser power: 2.5-4.5KW, powder feeding amount: 12-18g / min, swing amplitude: 15-40mm, swing speed: 20-60mm / min, powder feeding gas flow: 5.5-8.5L / min, shielding gas flow: 10-15L / min; more preferably: laser power: 3.0-4.0KW, powder feeding amount: 14-16g / min, swing amplitude: 20-35mm, swing speed: 30-50mm / min, powder feeding gas flow: 6.0-8.0L / min, shielding gas flow: 12-14L / min. The present invention does not specifically limit the specific types of the powder feeding gas and shielding gas, and they can be selected according to the technical common sense of those skilled in the art. The present invention controls the laser power of the laser cladding process according to the dilution rate of the cladding layer and the microscopic morphology of the dispersedly distributed cemented carbide particles, so as to avoid the melting of the cemented carbide particles under the action of the high-temperature beam due to excessive laser power, and the small hard particles cannot play the role of hard strengthening; the cladding thickness of the Fe-Ni-based titanium carbide coating can be adjusted by controlling the swing speed and the powder feeding amount; the width of the cladding layer during the cladding process can be adjusted by controlling the swing amplitude; and the Fe-Ni-based titanium carbide coating with excellent comprehensive performance can be obtained by controlling the parameters of the laser cladding process.
[0041] The Fe-Ni based titanium carbide coating provided by the present invention has a Rockwell hardness of up to 58-64HRC, and its wear resistance is between that of the laser cladding iron based titanium carbide cladding layer and the plasma cladding nickel based tungsten carbide coating, and has excellent performance; no cracks are generated on the surface of the cladding layer, and the TiC cemented carbide particles have good adhesion to the Fe-Ni base, and the entire cladding coating and the substrate show a metallurgical bond; the cost of using Fe-Ni based titanium carbide is higher than that of iron based titanium carbide, but the cost is greatly reduced compared to nickel based tungsten carbide, which meets the actual needs of the project.
[0042] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] An Fe-Ni based titanium carbide coating alloy powder for laser cladding is prepared by mixing the following raw materials: an iron based alloy powder, a nickel based alloy powder and a TiC powder;
[0045] The element composition of the iron-based alloy powder is, by mass percentage, C: 3.52%, O: 0.0271%, B: 2.06%, Si: 2.54%, Cr: 29.62%, Ni: 5.09%, Mo: 3.04% and the balance Fe; the average Rockwell hardness value of the iron-based alloy powder is 60HRC;
[0046] The element composition of the nickel-based alloy powder is, by mass percentage, C: 0.3%, Cr: 0.3%, B: 0.63%, Si: 1.36%, Fe: 0.55% and the balance Ni; the average Rockwell hardness value of the nickel-based alloy powder is 54HRC;
[0047] The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is 4:1;
[0048] The content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 45% by mass; the average Rockwell hardness value of the TiC powder is 62HRC;
[0049] The particle size of the iron-based alloy powder is 60-200 meshes, the particle size of the nickel-based alloy powder is 60-200 meshes, and the particle size of the TiC powder is 80-120 meshes; the particle size of the Fe-Ni-based titanium carbide coating alloy powder for laser cladding is 60-200 meshes.
[0050] Example 2
[0051] The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is 3:1;
[0052] Other conditions are the same as those in Example 1.
[0053] Example 3
[0054] The content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 55% by mass percentage;
[0055] Other conditions are the same as those in Example 1.
[0056] Example 4
[0057] The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is 3:1;
[0058] The content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 65% by mass percentage;
[0059] Other conditions are the same as those in Example 1.
[0060] Example 5
[0061] The content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 55% by mass percentage;
[0062] Other conditions are the same as those in Example 1.
[0063] Example 6
[0064] The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is 3:1;
[0065] The content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 35% by mass percentage;
[0066] Other conditions are the same as those in Example 1.
[0067] Example 7
[0068] The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is 3:1;
[0069] Measured by mass percentage, the content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 60%;
[0070] Other conditions are the same as those in Example 1.
[0071] Example 8
[0072] The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is 3:1;
[0073] Measured by mass percentage, the content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 50%;
[0074] Other conditions are the same as those in Example 1.
[0075] Comparative Example 1
[0076] An Fe-based titanium carbide coating alloy powder is prepared by mixing an Fe-based alloy powder and a TiC powder;
[0077] The element composition of the iron-based alloy powder is, by mass percentage, C: 3.52%, O: 0.0271%, B: 2.06%, Si: 2.54%, Cr: 29.62%, Ni: 5.09%, Mo: 3.04% and the balance Fe; the average Rockwell hardness value of the iron-based alloy powder is 60HRC;
[0078] In terms of mass percentage, the content of TiC powder in the Fe-based titanium carbide coating alloy powder for laser cladding is 45%; the average Rockwell hardness value of the TiC powder is 62HRC;
[0079] The particle size of the iron-based alloy powder is 60-200 meshes, the particle size of the TiC powder is 80-120 meshes; the particle size of the Fe-based titanium carbide coating alloy powder for laser cladding is 60-200 meshes.
[0080] Comparative Example 2
[0081] Measured by mass percentage, the content of TiC powder in the Fe-based titanium carbide coating alloy powder for laser cladding is 65%;
[0082] The other conditions were the same as those in Comparative Example 1.
[0083] Application Example 1
[0084] An Fe-Ni based titanium carbide coating is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided in Example 1 as a raw material;
[0085] The parameters of the laser cladding process are: laser power: 4.5KW, powder feeding amount: 18g / min, swing amplitude: 40mm, swing speed: 60mm / min, powder feeding gas is nitrogen, powder feeding gas flow rate: 8.5L / min, shielding gas is nitrogen, shielding gas flow rate: 12L / min.
[0086] The microstructure metallographic image of the Fe-Ni based titanium carbide coating prepared in Application Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that when the laser power is 4.5KW, the laser power is relatively high, and the particles have burning and recrystallization phenomena, which means that when the laser power continues to increase, the performance of the Fe-Ni-based titanium carbide coating will decrease rapidly.
[0087] Application Example 2
[0088] An Fe-Ni based titanium carbide coating is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided in Example 2 as a raw material;
[0089] The parameters of the laser cladding process are: laser power: 3.5KW, powder feeding amount: 16g / min, swing amplitude: 20mm, swing speed: 30mm / min, powder feeding gas is nitrogen, powder feeding gas flow rate: 6.5L / min, shielding gas is nitrogen, shielding gas flow rate: 12L / min.
[0090] The microstructure metallographic image of the Fe-Ni based titanium carbide coating prepared in Application Example 2 is as follows: Figure 2 As shown by Figure 2It can be seen that the particle burning phenomenon is significantly improved. It can be seen that after increasing the Fe powder content in the base powder and reducing the power to 3.5KW, even if the powder feeding amount is reduced, the swing amplitude and swing speed are reduced, the particle burning is lighter, but the hardness is reduced.
[0091] Application Example 3
[0092] An Fe-Ni based titanium carbide coating is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided in Example 3 as a raw material;
[0093] The parameters of the laser cladding process are: laser power: 4KW, powder feeding amount: 16g / min, swing amplitude: 35mm, swing speed: 50mm / min, powder feeding gas flow rate: 6.5L / min, shielding gas flow rate: 12 / min.
[0094] The microstructure metallographic image of the Fe-Ni based titanium carbide coating prepared in Application Example 3 is as follows: Figure 3 As shown by Figure 3 It can be seen that when the laser power is 4KW, the particles are burned and recrystallized, and black carbides are precipitated.
[0095] Application Example 4
[0096] An Fe-Ni based titanium carbide coating is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided in Example 4 as a raw material;
[0097] The parameters of the laser cladding process are: laser power: 3KW, powder feeding amount: 14g / min, swing amplitude: 25mm, swing speed: 30mm / min, powder feeding gas flow rate: 6.5L / min, shielding gas flow rate: 12L / min.
[0098] The microstructure metallographic image of the Fe-Ni based titanium carbide coating prepared in Application Example 4 is as follows: Figure 4 As shown by Figure 4 It can be seen that due to the increase in the content of iron-based powder and the decrease in cladding power, voids appear in the cladding layer.
[0099] Application Example 5
[0100] An Fe-Ni based titanium carbide coating is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided in Example 5 as a raw material;
[0101] The parameters of the laser cladding process are: laser power: 3.5 KW, powder feeding amount: 14 g / min, swing amplitude: 25 mm, swing speed: 40 mm / min, powder feeding gas flow rate: 6.5 L / min, and shielding gas flow rate: 12 L / min.
[0102] The microstructure metallographic image of the Fe-Ni based titanium carbide coating prepared in Application Example 5 is as follows: Figure 5 As shown by Figure 5 It can be seen that due to the high powder feeding amount and fast swing amplitude, the local cladding power is low and gaps appear at the junction of the cladding layer and the substrate.
[0103] Application Example 6
[0104] An Fe-Ni based titanium carbide coating is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided in Example 6 as a raw material;
[0105] The parameters of the laser cladding process are: laser power: 2.5 KW, powder feeding amount: 12 g / min, swing amplitude: 15 mm, swing speed: 20 mm / min, powder feeding gas flow rate: 5.5 L / min, and shielding gas flow rate: 12 L / min.
[0106] The microstructure metallographic image of the Fe-Ni based titanium carbide coating prepared in Application Example 6 is as follows: Figure 6 As shown by Figure 6 It can be seen that due to the low total cladding power, the particles are clear and continuous gaps appear at the junction of the cladding layer and the substrate.
[0107] Application Example 7
[0108] An Fe-Ni based titanium carbide coating is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided in Example 7 as a raw material;
[0109] The parameters of the laser cladding process are the same as those in Application Example 1.
[0110] Application Example 8
[0111] An Fe-Ni based titanium carbide coating is prepared by a laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding provided in Example 8 as a raw material;
[0112] The parameters of the laser cladding process are the same as those in Application Example 1.
[0113] Comparative application example 1
[0114] An Fe-based titanium carbide coating is prepared by a laser cladding process using the Fe-based titanium carbide coating alloy powder provided in Comparative Example 1 as a raw material;
[0115] The parameters of the laser cladding process are the same as those in Application Example 1.
[0116] The microstructure metallographic image of the Fe-based titanium carbide coating prepared in comparative application example 1 is as follows: Figure 7 As shown by Figure 7 It can be seen that the particles are almost not burned, but there is a clear boundary between the titanium carbide particles and the matrix, which also means that a higher cladding power is required to obtain a good cladding effect.
[0117] Comparative Application Example 2
[0118] An Fe-based titanium carbide coating is prepared by a laser cladding process using the Fe-based titanium carbide coating alloy powder provided in Comparative Example 2 as a raw material;
[0119] The parameters of the laser cladding process are the same as those of Comparative Example 1.
[0120] The hardness of the coatings prepared in Examples 1 to 6 and Comparative Application Example 1 was tested using a microhardness tester. The test results are shown in Table 1:
[0121] Table 1 Hardness of coatings prepared in Application Examples 1 to 6 and Comparative Application Example 1
[0122] Application Example 1 Application Example 2 Application Example 3 Application Example 4 Application Example 5 Application Example 6 Comparative application example 1 hardness 62.0HV 61.3HV 63.2HV 66.1HV 63.4HV 60.0HV 58.5HV
[0123] The wear resistance of the coating prepared in Example 1 and Comparative Application Example 1 was tested by a friction and wear testing machine. The model of the friction and wear testing machine is BD4603, the rotation speed is 2980rpm, the diameter of the sample during the test is 15.5mm, the load is 2.0Kg, and an 80# sanding belt machine is used for grinding. The model of the sanding belt is (Korea Deer Brand) DEERFOS YA531+, the size of the sanding belt is 100*912, and the mesh number of the sanding belt is 80 meshes. The test results are as follows: Figure 8 As shown. Figure 8 It can be seen that under higher power, the titanium carbide particles in the cladding layer prepared in Example 1 are less burned, and the hardness of the cladding layer matrix is not high, but its wear resistance is better than that of the Fe-Ni based TiC cladding layer in Example 1.
[0124] The wear resistance of the coating prepared in Examples 7 to 8 and Comparative Example 2 was tested by a friction and wear testing machine. The model of the friction and wear testing machine is BD4603, the rotation speed is 2980 rpm, the diameter of the sample during the test is 15.5 mm, the load is 2.0 kg, and an 80# sanding belt machine is used for grinding. The model of the sanding belt is (Korea Deer Brand) DEERFOS YA531+, the size of the sanding belt is 100*912, and the mesh number of the sanding belt is 80 meshes. The test results are as follows: Fig. 9 As shown. Fig. 9It can be seen that TiC particles are the determining factor affecting the wear resistance of the cladding layer. The higher the TiC content in the cladding layer, the better the wear resistance and the lower the wear loss.
[0125] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A Fe-Ni based titanium carbide coating alloy powder for laser cladding, prepared from the following raw materials: iron based alloy powder, nickel based alloy powder and TiC powder; The element composition of the iron-based alloy powder includes, by mass percentage: C: 3.0-4.0%, O < 0.05%, B: 1.5-2.5%, Si: 2.0-3.0%, Cr: 20-35%, Ni: 2.0-8.0%, Mo: 2.0-5.0% and the balance Fe; The element composition of the nickel-based alloy powder includes, by mass percentage, C: 0.2-0.5%, Cr: 0.2-0.5%, B: 0.4-0.8%, Si: 1.1-1.5%, Fe: 0.3-0.6% and the balance Ni; The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is (3-4):1; Measured by mass percentage, the content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 35-65%.
2. The Fe-Ni based titanium carbide coating alloy powder for laser cladding according to claim 1, characterized in that: The content of TiC powder in the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 40-60%.
3. The Fe-Ni based titanium carbide coating alloy powder for laser cladding according to claim 1, characterized in that: The element composition of the iron-based alloy powder is: C: 3.5-3.8%, O<0.04%, B: 2.0-2.3%, Si: 2.5-2.8%, Cr: 25-30%, Ni: 4.0-6.0%, Mo: 3.0-4.0% and the balance of Fe.
4. The Fe-Ni based titanium carbide coating alloy powder for laser cladding according to claim 1, characterized in that: The element composition of the nickel-based alloy powder is: C: 0.3-0.4%, Cr: 0.3-0.4%, B: 0.5-0.7%, Si: 1.2-1.4%, Fe: 0.4-0.6% and the balance Ni.
5. The Fe-Ni based titanium carbide coating alloy powder for laser cladding according to claim 1, characterized in that: The mass ratio of the iron-based alloy powder to the nickel-based alloy powder is 4:
1.
6. The Fe-Ni based titanium carbide coating alloy powder for laser cladding according to claim 1, characterized in that: The particle size of the Fe-Ni based titanium carbide coating alloy powder for laser cladding is 60-200 meshes.
7. An Fe-Ni based titanium carbide coating, prepared by laser cladding process using the Fe-Ni based titanium carbide coating alloy powder for laser cladding according to any one of claims 1 to 6 as raw material.
8. The Fe-Ni based titanium carbide coating according to claim 7, characterized in that: Parameters of the laser cladding process Including: laser power: 2.5~4.5KW, powder feeding amount: 12~18g / min, swing amplitude: 15~40mm, swing speed: 20~60mm / min, powder feeding gas flow: 5.5~8.5L / min, shielding gas flow: 10~15L / min.
9. The Fe-Ni based titanium carbide coating according to claim 8, characterized in that: Parameters of the laser cladding process Including: laser power: 3.0~4.0KW, powder feeding amount: 14~16g / min, swing amplitude: 20~35mm, swing speed: 30~50mm / min, powder feeding gas flow: 6.0~8.0L / min, shielding gas flow: 12~14L / min.
Citation Information
Patent Citations
Special-purpose iron-base powder for laser fast forming
CN101122018A
Alloy powder made of micro-nanometer particles through enhanced laser cladding and method for preparing same
CN103495737A